2011
DOI: 10.1097/cmr.0b013e32834b58fa
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-based vaccine in advanced melanoma

Abstract: Dendritic cells (DCs) are unique specialized antigen-presenting cells capable of priming naive T cells and inducing antigen-specific cytotoxic T lymphocytes. This study presents an update of clinical results from a DC-based phase I-II clinical vaccine trial in stage IV melanoma. From 2003 to 2010, 27 patients with metastatic melanoma were treated with mature DCs pulsed with autologous tumor lysate and keyhole limpet hemocyanin and with subcutaneous low-dose interleukin-2. Delayed-type hypersensitivity (DTH) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
1
26
1
1
Order By: Relevance
“…Like de Vries et al [17], we saw that patients who developed anti-tumor immunity after vaccination experienced a better clinical outcome [16,18]. In particular, we observed that patients developing delayed type hypersensitivity (DTH) against autologous tumor lysate or keyhole lympet hemocyanin (KLH) after at least four courses of the vaccine showed a median overall survival (OS) of 22.9 months compared to the 4.8 months of DTH-negative cases (Log-rank test, p = 0.007) [16].…”
Section: Background and Rationalementioning
confidence: 76%
See 3 more Smart Citations
“…Like de Vries et al [17], we saw that patients who developed anti-tumor immunity after vaccination experienced a better clinical outcome [16,18]. In particular, we observed that patients developing delayed type hypersensitivity (DTH) against autologous tumor lysate or keyhole lympet hemocyanin (KLH) after at least four courses of the vaccine showed a median overall survival (OS) of 22.9 months compared to the 4.8 months of DTH-negative cases (Log-rank test, p = 0.007) [16].…”
Section: Background and Rationalementioning
confidence: 76%
“…Since 2001, patients with advanced melanoma enrolled onto our phase II clinical studies have been administered autologous DC loaded with autologous tumor lysate/homogenate matured with a cytokine cocktail, showing a clinical benefit (PR + SD) in 55.5% of evaluable cases [15,16]. …”
Section: Background and Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Cutaneous DTH could be used as an indicator to evaluate immune therapy (35), as well as being a predictor of survival (36). In 27 patients with stage IV MM receiving a DC vaccine to induce DTH, the median survival time was 22.9 months (n=19) in DTH-positive patients and 4.8 months in DTH-negative patients (37). Similarly, in the present study, the extent of the DTH reaction was associated with OS and DFS.…”
Section: Discussionmentioning
confidence: 99%